2010
DOI: 10.1242/jcs.071373
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor Znf219 regulates chondrocyte differentiation by assembling a transcription factory with Sox9

Abstract: SummarySox9 is an essential transcription factor for chondrogenesis by regulating the expression of chondrogenic genes. However, its regulatory mechanism is not fully understood. To address this, we attempted to identify the transcriptional partners of Sox9 by screening the cDNA library of the chondrogenic cell line ATDC5 using the collagen 21 (Col21) gene promoter fused to a luciferase reporter gene. One of the positive clones encoded the Znf219 gene. Whole mount in situ hybridization experiments indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
53
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 65 publications
3
53
0
Order By: Relevance
“…Thus, the identification and characterization of novel transcription factors involved in these processes will contribute to a better understanding of endochondral ossification. Numerous attempts have been made to identify these and we previously identified several transcription factors using a high-throughput assay system [21][22][23][24] and Solexa deep-sequencing technology 25 . However, the transcriptional networks of endochondral ossification are still not fully elucidated.…”
mentioning
confidence: 99%
“…Thus, the identification and characterization of novel transcription factors involved in these processes will contribute to a better understanding of endochondral ossification. Numerous attempts have been made to identify these and we previously identified several transcription factors using a high-throughput assay system [21][22][23][24] and Solexa deep-sequencing technology 25 . However, the transcriptional networks of endochondral ossification are still not fully elucidated.…”
mentioning
confidence: 99%
“…18), which links Sox9-mediated transcription with RNA processing during chondrogenesis, and Znf219 (ref. 19) are members of the Sox9-assembled transcriptional complex.…”
mentioning
confidence: 99%
“…SOX9 has been also identified as a transcription factor that specifically binds to the Col2a1 gene [64]. These findings indicate that SOX9 is an essential transcription factor that initiates endochondral ossification by upregulating early chondrogenic genes including Col2a1, Col11a2, and aggrecan [64,65]. Sox5 and Sox6, known to be Sox9 target genes [63], are required for chondrocyte differentiation, because Sox5/Sox6 double knockout mice exhibit pronounced cartilage formation defects (Fig.…”
Section: Coordination Of Endochondral Ossification By Transcriptionalmentioning
confidence: 94%
“…A high-throughput biological assay using the Col2a1 luciferase reporter gene revealed that p54 nrb , ARID5A, and ZNF219 form a transcriptional complex with SOX9 during chondrocyte differentiation (Fig. 3) [65,[70][71][72]. Gene profiling by microarray and RNA-Seq experiments have showed that WWP2 and ARID5B are also required for the SOX9-regulated chondrogenesis (Fig.…”
Section: Coordination Of Endochondral Ossification By Transcriptionalmentioning
confidence: 99%